2016
DOI: 10.1016/j.foreco.2016.05.025
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Robinia pseudoacacia afforestation on soil and vegetation properties in the Loess Plateau (China): A chronosequence approach

Abstract: a b s t r a c tRevegetation is one of the primary management approaches for solving the problems caused by severe soil erosion worldwide. Robinia pseudoacacia was considered a promising tree for afforestation in the highly eroded region of the Loess Plateau due to its fast growth and ability to fix atmospheric nitrogen. However, its beneficial role protecting soils from erosion has been now questioned and several negative effects on soil and vegetation have been described. In this study we aimed to analyze the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
35
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(47 citation statements)
references
References 46 publications
(69 reference statements)
4
35
1
1
Order By: Relevance
“…On the one hand, afforestation may be feasible in areas where the MAP is higher than 520 mm. The reduction of plant density and increasing species diversity based on prudent tree species selection are critical strategies for this region [21]. Furthermore, new research has shown that planted forests have a less positive effect on carbon sequestration; however, they lead to significant water yield reduction in contrast to natural forests [55].…”
Section: Implications For Future Restoration Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, afforestation may be feasible in areas where the MAP is higher than 520 mm. The reduction of plant density and increasing species diversity based on prudent tree species selection are critical strategies for this region [21]. Furthermore, new research has shown that planted forests have a less positive effect on carbon sequestration; however, they lead to significant water yield reduction in contrast to natural forests [55].…”
Section: Implications For Future Restoration Strategiesmentioning
confidence: 99%
“…Under these projects, afforested areas increased from 14.8% to 21.7% by 2010, and introduced plantations became the dominant vegetation [8]. However, large-scale afforestation with introduced vegetation such as korshinsk peashrub (Caragana korshinskii, CK), sea buckthorn (Hippophae rhamnoides, HR), and black locust (Robinia pseudoacacia, RP), required excessive amounts of soil water [21][22][23], which gradually led to the formation of dry soil layers widely across the Loess Plateau [7]. These dry soil layers have become an ominous indicator of the soil desiccation phenomenon and ecosystem vulnerability in the Loess Plateau [8].…”
Section: Introductionmentioning
confidence: 99%
“…The reforestation remains one of the most effective strategies for coping with climate change (Jean-Francois et al, 2019), which is also the most effective management method to solve the problems of soil erosion all over the world (Clemente et al 2004; Kou et al 2016). It is considered to be an effective strategy to prevent soil erosion and soil degradation, and to promote the restoration of degraded ecosystems (Zhang et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Afforestation is an efficient measure to repair destroyed natural ecosystems, which occurs by converting cropland into perennial vegetation land, has great impacts on plant primary productivity and soil physicochemical properties (i.e., soil bulk density, aggregation, soil nutrient pools, and biodiversity) [1][2][3] and in turn, influences soil biological activity, such as soil enzyme activity and microbial biomass [4,5]. Soil enzyme activities in changing land-use types have attracted special attention for this topic's relevance in soil ecosystem dynamics and ecosystem sustainability [6,7].…”
Section: Introductionmentioning
confidence: 99%